Crustal controls on light noble gas isotope variability along the Andean Volcanic Arc - Lages, Joao (2021)
This study combines new noble gas data from fluid inclusions in minerals from Sabancaya, Ubinas, and El Misti (CVZ, Peru) and Villarica (South Chile, SVZ) with a revised noble gas compilation in the Andes, to identify systematic along arc variations in helium isotope compositions. We find 3He/4He ratios varying from 8.8 RA (Colombia) to 7.4 RA (Ecuador) within the NVZ, and only as high as 6.4 RA in the CVZ (RA is the atmospheric 3He/4He ratio of 1.39 × 10–6). These distinct isotope compositions cannot be explained by variable radiogenic 4He production via slab fluid transport of U and Th in the mantle wedge, since both NVZ and CVZ share similar slab sediment inputs (Th/La ≈ 0.08–0.13). Instead, the progressively more radiogenic 3He/4He signatures in Ecuador and Peru reflect 4He addition upon magma ascent/storage in the crust, this being especially thick in Peru (>70 km) and Ecuador (>50 km) relative to Colombia (∼30–45 km). The intermediate compositions in the North (8.0 RA) and South (7.9 RA) Chile, both high sediment flux margins, mostly reflect a more efficient delivery of radiogenic He in the wedge from the subducted (U-Th-rich) terrigenous sediments. Our results bring strong evidence for the major role played by crustal processes in governing noble gas compositions along continental arcs.